2016
DOI: 10.1007/s10549-016-3756-5
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of toxicity profiles between the lower and standard dose capecitabine in breast cancer: a systematic review and meta-analysis

Abstract: Purpose Capecitabine 1,000 mg/m2 bid × 14 days every 21 days (14/21) has been reported to have similar efficacy but more favorable toxicity profile than the approved dosage of 1,250 mg/m2. However, a dose-toxicity relationship of capecitabine in breast cancer patients has not been fully elucidated. We performed a systematic review and meta-analysis to compare a safety profile between capecitabine starting dose of 1,000 and 1,250 mg/m2 bid. Methods Studies were identified using PubMed, ASCO and San Antonio Br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 55 publications
5
9
0
Order By: Relevance
“…The pooled grade 3/4 AEs rate of 29.5% (95% CI 21.1–39.5) seemed to be a little high; this may be attributed to our taking into account the different kinds of observed AEs. Similar to the findings of our study, results from a recently published meta-analysis also show a better toxicity profile with the use of a lower dosage of capecitabine [ 47 ]. Most of the of MBC patients in this study were either pretreated or had chemotherapy resistance; these findings plus the OS data are optimistic and are further supported by the results of a recent, randomized, phase II study (NCT0141771) aimed to prove that MCT was effective and less toxic in comparison to standard chemotherapy [ 48 ].…”
Section: Discussionsupporting
confidence: 91%
“…The pooled grade 3/4 AEs rate of 29.5% (95% CI 21.1–39.5) seemed to be a little high; this may be attributed to our taking into account the different kinds of observed AEs. Similar to the findings of our study, results from a recently published meta-analysis also show a better toxicity profile with the use of a lower dosage of capecitabine [ 47 ]. Most of the of MBC patients in this study were either pretreated or had chemotherapy resistance; these findings plus the OS data are optimistic and are further supported by the results of a recent, randomized, phase II study (NCT0141771) aimed to prove that MCT was effective and less toxic in comparison to standard chemotherapy [ 48 ].…”
Section: Discussionsupporting
confidence: 91%
“…This suggests that fatigue is quite common and other clinical factors, including the neurophysiological effects of the breast cancer itself, likely contribute to the experience of fatigue rather than the effects of chemotherapy alone. We found that an increase in fatigue was reported during the chemotherapy treatment period, which supported the study hypotheses and was consistent with prior reports of fatigue in the context of chemotherapy . A decrease in fatigue severity, which occurred for most women by 1‐year post‐chemotherapy indicates that chemotherapy did not produce long‐term exacerbation of fatigue beyond the levels experienced prior to chemotherapy.…”
Section: Discussionsupporting
confidence: 90%
“…36 In this scenario, oral therapies limit the number of ambulatory visits thus reducing the nosocomial risk which is mostly related to hospital access, and can frequently be proposed as good alternatives to intravenous treatments, with evidence suggesting that low-dose or metronomic schedules may be as effective as standard scheduling, with lesser side effects. 37,38 Therefore, whenever available oral therapy should be preferred over intravenous therapy, and telephone and/or web-based contact should be planned to follow the course of therapy.…”
Section: How Can Infection Be Prevented?mentioning
confidence: 99%